Economic impact of open grazing policy in Anambra State - Muoneke, Chukwuemeka Vincent; Okoli, Uju Victoria (Social Science Research, 2022)
Open grazing is the age-old practice of herders roaming about with their animals in open fields, plains and nearby bushes in search of pasture for the animals. In Nigeria recently, there seem to be a lot of attention drawn to this phenomenon. This study attempted to ascertain if farmers in Anambra State were aware of open grazing policy and then determine the economic impact of the policy on agricultural produce and food prices in Anambra state. The origin, immediate and remote causes of Fulani herders/farmers conflict with both farmers and thehost communities in Nigeria were studied.Using cluster sampling technique, Anambra State was chosen to represent Nigeria.The research adopted the Karl Marx Conflict theory as the theoretical frame work while focus group discussion, face to face interview to support the data gotten from questionnaire were employed in data collection and analysis. The findings show that farmers in Anambra state are fully aware of the open grazing policy of the government andthere is significant negative impact of open grazing policy on agricultural produce and food prices in Nigeria. The study then recommends that Government should ban open grazing of cattle by the citizens and establish ranches to prevent encroachment into farmlands. Government should also establish a peace mediation committee responsible for reconciliation between the Fulani herders and farmers in the state, in order to reach a lasting solution.